Māori Realities, Intimacies, and Sexual Expressions: Reconceptualising Consent To Uphold Kaumātua Mana in Aged Residential Care - McDonald, Sandra; Henrickson, Mark; Cook, Catherine; Schouten, Vanessa (SAGE Publications, 2023)
Increasingly, kaumātua (Māori elders) in Aotearoa (New Zealand) live apart from whānau (Māori extended family) in residential care, where policies are shaped by post-colonial legislation and ethical principles that privilege individual rights over Indigenous priorities and rights. The communal context of residential care has created late-life opportunity for intimacy and sexual expression with new partners. These issues are addressed in the international literature, highlighting the benefits and complexities. Literature report there may be clashes between resident and family members’ wishes, and tensions around privacy and consent. This article considers survey data and semi-structured interviews with kaimahi (Māori care workers) and a kaumātua who were part of a larger study of staff, residents, and family in the residential aged care context. Post-colonial individualistic rights-based approaches do not necessarily fit with a Māori worldview. A Māori-led articulation of consent is essential to uphold the mana (authority, influence, power) of kaumātua and whānau.
Keywords: 2002 Cultural Studies; 4702 Cultural studies; dementia; indigenous ethics; intimacy; Māori; sexuality; whānau